Superconductivity in ordered Li–Al–B compounds - K. Hussain; S. J. Donaldson; E. Karaca; P. J. P. Byrne; P. J. Hasnip; M. I. J. Probert (Scientific Reports)
Abstract Using first principles calculations, we show that $$\hbox {Li}_x\hbox {Al}_y\hbox {B}_{2(x+y)}$$ materials have strong electron-phonon coupling, with many having a superconducting critical temperature ( $$T_c$$ ) that exceeds that of the more familiar $$\hbox {MgB}_2$$ at ambient pressure. In particular, we find that $$\hbox {LiAlB}_4$$ is the most stable member of the family, with $$T_c > 44\,\hbox {K}$$ whilst the peak $$T_c$$ is with $$\hbox {Li}_3\hbox {AlB}_8$$ which has $$T_c > 77\,\hbox {K}$$ . Our results reveal that these materials are both thermodynamically and dynamically stable, with strong electron-phonon coupling, indicating significant potential for practical superconducting applications.